2018
DOI: 10.1097/inf.0000000000001968
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Fungal Infections in Neonates in Canada

Abstract: The overall incidence of IFI in neonates was low in Canada in comparison to other large population cohort studies; however, the mortality and morbidity remained high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 39 publications
6
34
1
1
Order By: Relevance
“…Similar studies in Egypt 12 , Australia 13 , and Mexico 19 have also reported results consistent with the above publications, confirming the risk of prolonged exposure to antibiotics in VLBW neonates. The results of these publications [9][10][11][12][13][17][18][19] are similar to the findings of this study, in which it was observed that prolonged exposure (≥5 days) to empirical antibiotics after birth increased the risk of late sepsis and NEC, OR=1,88, and OR=9,71 respectively. It should be noted that in all these reports [9][10][11][12][13][17][18][19] , the studied population has similar characteristics (very low or extreme low weight NBs).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar studies in Egypt 12 , Australia 13 , and Mexico 19 have also reported results consistent with the above publications, confirming the risk of prolonged exposure to antibiotics in VLBW neonates. The results of these publications [9][10][11][12][13][17][18][19] are similar to the findings of this study, in which it was observed that prolonged exposure (≥5 days) to empirical antibiotics after birth increased the risk of late sepsis and NEC, OR=1,88, and OR=9,71 respectively. It should be noted that in all these reports [9][10][11][12][13][17][18][19] , the studied population has similar characteristics (very low or extreme low weight NBs).…”
Section: Discussionsupporting
confidence: 87%
“…The results of these publications [9][10][11][12][13][17][18][19] are similar to the findings of this study, in which it was observed that prolonged exposure (≥5 days) to empirical antibiotics after birth increased the risk of late sepsis and NEC, OR=1,88, and OR=9,71 respectively. It should be noted that in all these reports [9][10][11][12][13][17][18][19] , the studied population has similar characteristics (very low or extreme low weight NBs). On the other hand, there is a high rate of positive blood cultures (65.6%) among the cases of late clinical sepsis in this study, where the most frequently isolated microorganism is the coagulase-negative Staphylococcus, which is consistent with what has been reported in other studies 9,11,13 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…care units (NICUs) in Canada revealed that although C. albicans remains the major cause of neonatal invasive Candida disease (59%), C. parapsilosis is also highly prevalent (21%) (54). Recently, cases from European countries were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…11 Furthermore, antibiotic use in VLBW infants without culture proven sepsis or NEC, was found to be associated with an adverse composite neonatal outcome defined as mortality or major morbidity, including persistent periventricular echogenicity or echolucency on neuroimaging, chronic lung disease, and stage-3 or higher retinopathy of prematurity. 12 Adjuvants in the diagnosis of culture-negative sepsis: Molecular techniques, such as PCR, are considered more sensitive and rapid than blood cultures and may identify ultra-low bacteremia that may not require treatment. A Cochrane review concluded that they may perform well as "add-on" tests.…”
Section: Definitionsmentioning
confidence: 99%